Black stone – a natural remedy for premature ejaculation and performance enhancement, or maybe not?. (August 2014) - Bush, Carly; O'Farrell, Nigel
We describe the use of a non-prescribed aid (Black stone) for premature ejaculation that resulted in a chemical burn on the penis with an appearance similar to severe balanitis.